Religious beliefs; Barrier or mainspring to organ donation - Amin Zarghami; Nozar Dorestan; Mohammad Bahadoram; Samaneh Bahadoram (Society of Diabetic Nephropathy Prevention, 2018)
Implication for health policy/practice/research/medical education: More studies are needed to characterize the associated factors in each unique culture and society for promoting the positive attitudes regarding tissue and organ transplantation for various life threatening and incurable diseases